THE STUDY OF CHEMICAL TRANSFORMATIONS: AN ANALYSIS OF CONCEPTUAL CHANGE AT THE BEGINNING OF HIGH SCHOOL - da Silva, Daniela Rodrigues; Pozo, Juan Ignacio; Del Pino, José Cláudio (Investigações em Ensino de Ciências, 2020)
To understand the phenomenon of chemical transformations in high school, students need to comprehend the idea of conservation of matter and of non-conservation of substances during the process.By considering the hypothesis of hierarchical integration, this article aims at showing the conceptual changes produced by junior high school students through the use of a Teaching and Learning Proposal (TLP). Due to the learning difficulties presented by the students, the TLP was structured around three assumptions which are considered basic for the studying of chemical transformations: concepts (conceptual cores); approach models (macroscopic, symbolic, submicroscopic); and strategies (problem solving and counter suggestion). Qualitative research, characterized as a case study, presents the comparison between pre and posttests, in addition to the microgenetic analysis of learning, which evaluates in detail how these changes occur in a given period of time. The research was carried out with four volunteer students in four individual meetings (sessions) organized in three stages: pre-test, development of the TLP and posttest. Content analysis was the methodology employed to analyze the outcomes. Results show that both the individual theories explained by each student and their constructions involve a process that encompasses the elaboration of models with different levels of complexity, which coexist and are mobilized according to the problems proposed, being structured by a mixture of ideas constituted by implicit theories and scientific theories, that is, in the process of conceptual change, the students built new conceptual structures (each in their own time), without abandoning those that already existed, so that, they gradually differentiated and redesigned their interpretations aimingto the understanding and use of theories organized around scientifically accepted models.